Evidence for Bell-Shaped Dose-Response Emetic Effects of Temsirolimus and Analogs: The Broad-Spectrum Antiemetic Efficacy of a Large Dose of Temsirolimus Against Diverse Emetogens in the Least Shrew (Cryptotis parva) - Belkacemi, Louiza; Sun, Yina; Darmani, Nissar A. (Frontiers in Pharmacology, 2022)
Temsirolimus is a prodrug form of sirolimus (rapamycin). With its analogs (everolimus, ridaforolimus, and rapamycin), they form a group of anticancer agents that block the activity of one of the two mammalian targets of rapamycin (mTOR) complexes, mTORC1. We investigated the emetic potential of varying doses (0, 0.5, 1, 2.5, 5, 10, 20, and 40 mg/kg, i.p.) of temsirolimus in the least shrew. Temsirolimus caused a bell-shaped and dose-dependent increases in both the mean vomit frequency and the number of shrews vomiting with maximal efficacy at 10 mg/kg (P < 0.05 and P < 0.02, respectively). Its larger doses (20 or 40 mg/kg) had no significant emetic effect. We also evaluated the emetic potential of its paralogs (5, 10 and 20 mg/kg, i.p.), all of which exhibited a similar emetic profile. Our observational studies indicated that temsirolimus can reduce shrew motor activity at 40 mg/kg, and subsequently we examined the motor effects of its lower doses. At 10 and 20 mg/kg, it did not affect the spontaneous locomotor activity (distance moved) but attenuated the mean rearing frequency in a U-shaped manner at 10 mg/kg (P < 0.05). We then determined the broad-spectrum antiemetic potential of 20 mg/kg (i.p.) dose of temsirolimus against diverse emetogens including selective and non-selective agonists of: i) dopaminergic D2/3 receptors (apomorphine and quinpirole); ii) serotonergic 5-HT3 receptors [5-HT (serotonin) and 2-Methyl-5-HT]; iii) cholinergic M1 receptors (pilocarpine and McN-A-343); iv) substance P neurokinin NK1 receptors (GR73632); v) the L-type calcium (Ca2+) channel (LTCC) (FPL64176); as well as the sarcoplasmic endoplasmic reticulum Ca2+ ATPase inhibitor, thapsigargin; the CB1 receptor inverse agonist/antagonist, SR141716A; and the chemotherapeutic cisplatin. Temsirolimus prevented vomiting evoked by the above emetogens with varying degrees. The mechanisms underlying pro- and antiemetic effects of temsirolimus evaluated by immunochemistry for c-fos expression demonstrated a c-fos induction in the AP and NTS, but not DMNX with the 10 mg/kg emetic dose of temsirolimus, whereas its larger antiemetic dose (20 mg/kg) had no significant effect. Our study is the first to provide pre-clinical evidence demonstrating promising antiemetic potential of high doses of temsirolimus and possibly its paralogs in least shrews.